Unlocking expertise: the application of threshold concepts in scenario simulations in undergraduate clinical teaching - Ma, Dandan; Su, Ning; Hou, Rui; Wan, Yanyan; He, Zhuoran; Lan, Jinzhong; Xiao, Guizhen; Peng, Mian (Frontiers in Medicine, 2025)
BackgroundThreshold concepts, as a transformative learning approach, are crucial for mastering new knowledge and skills. They help students change their understanding of subjects and promote the development of professional competencies. This study aims to identify and understand the key threshold concepts in undergraduate clinical medical education and to explore their effectiveness in scenario-based simulation teaching.MethodsUsing a comparative experimental design, students were divided into two groups: one receiving threshold concept training and the other receiving traditional reinforcement training. The study combined scenario-based simulation, semi-structured interviews, and open-text surveys to assess student performance before and after training.ResultsStudents who received threshold concept training performed significantly better in tests than those in the traditional methods group. In Case 1, the threshold concept group scored 251(203, 259), significantly higher than the traditional methods group’s 201(181, 249) (p < 0.05). In Case 2, the threshold concept group scored 245(236, 251), significantly higher than the traditional methods group’s 232(228, 237) (p < 0.05). The results indicate that threshold concept training significantly improves student test scores, with statistically significant differences.ConclusionThis study identified key threshold concepts in undergraduate clinical education and validated their effectiveness in scenario-based simulation teaching. Threshold concepts not only guide the development of disease diagnosis and treatment skills but also provide new directions for teaching design and learning activities, facilitating the transition of medical students into competent doctors.